Parenthood as intended: Reproductive responsibility, moral judgements and having children 'by accident'. Issue 1 (January 2020) - Pralat, Robert
What does it mean to have a child 'by accident'? And why is parenthood so often described as happening 'accidentally', even when it is likely to involve at least some degree of intention? Drawing on interviews conducted in England and Wales with lesbians and gay men who do not have children but may have them in the future, this article explores the meanings of the notion that, as a same-sex couple, 'you can't have a child by accident' – a comment that interviewees frequently made unprompted when they were asked about the possibility of becoming parents. My data show that referring to 'accidental parenthood' is a common way of distinguishing one's experience of early adulthood from that of heterosexual people, especially among white, middle-class lesbians. As a closer reading of the data also suggests, parenthood that arguably happens by accident is often neither unforeseen nor unfortunate, and its currency as a point of reference reveals a powerful cultural narrative. When a wide range of reproductive behaviours are often deemed irresponsible because of their broadly defined timing, describing a pregnancy as an accident obscures responsibility. I argue that, to a certain extent, the discourse of accidental parenthood can serve to prevent moral judgements about reproductive decisions. Consequently, however, the 'inability' to have a child by accident makes the prospect of creating a family not only more complicated but also subject to greater scrutiny.